DOMESTIKASI IKAN TAPAH (Wallago leeri) DENGAN JUMLAH PEMBERIAN PAKAN YANG BERBEDA - Triwibisono, Jarot; Tang, Usman M.; ', Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from February to April 2015 at Taman Karya Hatchery, Pekanbaru-Riau. This research aims to determine the amount of feed appropriate and optimal for the growth and survival rate of fish tapah (Wallago leeri). The method used is experiments with 3 trial and 3 replications. The treatment are P1 = 3% dosage of the weight biomass, P2 = 5% dosage of the weight biomass and P3 = 7% dosage of the weight biomass. The results showed that the best treatment is P2 (5% dosage of the weight biomass) with the absolute growth weight of 34.5 grams, the absolute length of 6.0 cm, and a daily growth rate of 1.2%. The best results on feed efficiency and survival rate is P1 treatment of 11.9% and 100%.Keyword : Wallago leeri, Dosage fish trash, Domestictation